Internal combustion engine to electric vehicle retrofitting: Potential customer’s needs, public perception and business model implications - Hoeft, Fabian (Transportation research interdisciplinary perspectives, 2021)
Road transport is a major CO2 emission contributor globally. Driven by political incentives, the automotive industry is shifting from internal combustion engine (ICE) vehicles to electric vehicles (EVs). Despite substantial investments, EVs account for less than one per cent of road vehicles in most countries. Employing a sequential mixed-methods study, this paper investigates ICE to EV retrofitting, a potential solution to improve the transition to widespread adoption of EVs, using the case of Germany. First, seven semi-structured interviews with potential customers and industry experts served the subject exploration. Second, survey data from 76 potential customers, obtained using an online questionnaire, quantified perceptions and retrofitting requirements. Thematic analysis, statistical techniques and data triangulation provided rich insights. Informed by industry transition, transportation and strategy literature, this study contributes to the largely unexplored field of ICE to EV retrofitting. This paper investigates how a viable business model can look like, paying particular attention to customer needs and public perception. The business model implications highlight how a company can set up and integrate ICE to EV conversion into existing market structures.